Metagenomic next-generation sequencing indicates more precise pathogens in patients with pulmonary infection: A retrospective study - Wu, Dengfeng; Wang, Wei; Xun, Qiufen; Wang, Hongluan; Liu, Jiarong; Zhong, Ziqing; Ouyang, Chao; Yang, Qing (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To evaluate the diagnostic performance of mNGS in patients suspected with pulmonary infection. Methods: From April 2019 to September 2021, 502 patients with suspected pneumonia undergoing both mNGS of bronchoalveolar lavage fluid(BALF) and conventional microbiological tests (CMTs) were classified into different groups based on the comorbidities. The diagnostic performance was compared between mNGS and CMTs. Clinical comprehensive analysis was regarded as reference standard. Result: The diagnostic accuracy and sensitivity of mNGS were 74.9% (95% confidence interval [CI], 71.7-78.7%) and 72.5% (95% CI, 68.2-76.8%) respectively, outperformed those of CMTs (36.9% for diagnostic accuracy, 25.4% for sensitivity). In most of the pathogens, the detection rate of mNGS was higher than CMTs. Polymicrobial infections most often occurred in immunocompromised patients (22.1%). However, only 2.3% patients without underlying diseases developed polymicrobial infection. Besides, the spectrums of pathogens also varied in different groups. Importantly, the positive predictive values (PPVs) of mNGS were observed discrepant in different pathogens: 94.9% (95%CI 89.1-100%) for Mycobacterium tuberculosis, 86.2% (95%CI,72.9-99.6%) for Chlamydia psittaci, 86.0% (95%CI, 76.0-96.0%) for Aspergillus, and 67.6% (95%CI, 51.1-84.2%) for Non-mycobacterium tuberculosis, 67.3% (95%,54.1-80.5%) for Pneumocystis jeroveci; as for bacteria, the PPVs also show differences in different types of bacteria. Conclusion: mNGS of BALF can highly enhance the accuracy and detection rate of pathogens in patients with pulmonary infection. Besides, the comorbidities and the types of pathogens should be taken into consideration when interpreting the report of mNGS.